1988
DOI: 10.7164/antibiotics.41.1029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in vitro and in vivo activity of novel 9-deoxo-9a-aza-9a-homoerythromycin A derivatives; A new class of macrolide antibiotics, the azalides.

Abstract: A series of erythromycin A-derived semisynthetic antibiotics, featuring incorporation of a basic nitrogen atom into a ring expanded (15-membered) macrocyclic lactone, have been prepared and biologically evaluated. Semisynthetic modifications focused upon (1) varied substitution at the macrocyclic ring nitrogen and (2) epimerization or amine substitution at the C-4" hydroxyl site within the cladinose sugar. In general, the new azalides exhibit improved Gram-negative potency, expanding the spectrum of erythromyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
102
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(105 citation statements)
references
References 11 publications
0
102
0
1
Order By: Relevance
“…Using primary cultures of rat fetal fibroblasts, we recently reported that the dicationic acid-stable macrolide antibiotic, azithromycin [31,32], markedly inhibits fluid-phase uptake of horseradish peroxidase (HRP) and subsequent transfer to lysosomes, without affecting regurgitation [33]. It was also noticed that azithromycin caused an extensive vacuolation of late endocytic compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Using primary cultures of rat fetal fibroblasts, we recently reported that the dicationic acid-stable macrolide antibiotic, azithromycin [31,32], markedly inhibits fluid-phase uptake of horseradish peroxidase (HRP) and subsequent transfer to lysosomes, without affecting regurgitation [33]. It was also noticed that azithromycin caused an extensive vacuolation of late endocytic compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Azithromycin is a dicationic derivative of erythromycin A [1,2] which avidly accumulates in tissues [3,4] and in cultured mammalian cells, reaching intracellular to extracellular concentrations ratios of 100 and more [5]. Cell fractionation studies show that the bulk of the drug accumulated by cells localizes in the lysosomes [6].…”
Section: Introductionmentioning
confidence: 99%
“…In 1986 Pfizer, whose scientists also worked on this compound class [24,25], decided to licence-in azithromycin from PLIVA for worldwide markets. During the process development, 8 was first isolated as the anhydrous substance [14].…”
Section: N-substituted Azalide Derivatives and Azithromycinmentioning
confidence: 99%
“…Initial derivatives targeting the hydroxyl groups were esters: mono-, di-or tri-acetyl on the 2Ј-O-, 4Љ-O-and 11-O-hydroxyl groups, which were prepared using acetic anhydride with pyridine [32]. Reaction of 8 or its diacetyl derivative with ethylene carbonate and potassium carbonate yielded the corresponding 11,12-carbonates (25) or its diacetyl derivatives (Fig. 7).…”
Section: O-substitutedmentioning
confidence: 99%
See 1 more Smart Citation